Knowledge Management Strategies For Organizational Change: Study On Higher Education Organizations In Medan - Ardiani, Winda; Sunaryo, Sunaryo; Tumanggor, Boy Rizky (Jurnal Ekonomi, 2024)
Knowledge management is one of the concepts that is currently widely used by organizations, including Higher Education organizations to manage knowledge in order to improve the knowledge and abilities of lecturers comprehensively, so that it will be easier for organizations to make changes in accordance with current demands. This research is an exploratory study on knowledge management and change in higher education organizations. The approach used is qualitative, making it easier to explore thoroughly. To collect data, interviews were used with two key informants who understood knowledge management and change, as well as the leaders.  The results of the study show that higher education service organizations in Medan are less able to manage existing knowledge management with all the resources they have, so they are less able to make the changes needed today to become a quality and superior Higher Education Organization. Therefore, the change to become a quality and superior Higher Education Organization must be the concern of the entire community of Higher Education Organizations in Medan